2023
DOI: 10.3171/2022.6.jns212921
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of the Rotterdam CT score in the prediction of intracranial hypertension following severe traumatic brain injury

Abstract: OBJECTIVE Severe traumatic brain injury (TBI) is associated with intracranial hypertension (ICHTN). The Rotterdam CT score (RS) can predict clinical outcomes following TBI, but the relationship between the RS and ICHTN is unknown. The purpose of this study was to investigate clinical and radiological factors that predict ICHTN in patients with severe TBI. METHODS The authors performed a single-center retrospective review of patients who, between 2018 and 2021, had an intracranial pressure (ICP) monitor place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In 2005, the Rotterdam CT score, which is composed of the status of basal cisterns, midline shift, and types of mass lesions or intracranial hemorrhage, was developed for traumatic brain injury (TBI) ( 7 ). Recent studies have further confirmed the predictive value of the Rotterdam CT score for intracranial hypertension and its prognostic ability in patients undergoing DC following TBI ( 8 , 9 ). Thus, some characteristics (especially the status of cisterns and midline shift) in the Rotterdam CT score might be important replenishments for the prognosis prediction of LHIs in terms of their reflection of occupying effects and established predictive capability in potentially intracranial hypertension.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In 2005, the Rotterdam CT score, which is composed of the status of basal cisterns, midline shift, and types of mass lesions or intracranial hemorrhage, was developed for traumatic brain injury (TBI) ( 7 ). Recent studies have further confirmed the predictive value of the Rotterdam CT score for intracranial hypertension and its prognostic ability in patients undergoing DC following TBI ( 8 , 9 ). Thus, some characteristics (especially the status of cisterns and midline shift) in the Rotterdam CT score might be important replenishments for the prognosis prediction of LHIs in terms of their reflection of occupying effects and established predictive capability in potentially intracranial hypertension.…”
Section: Introductionmentioning
confidence: 81%
“…The first part was the evaluation of ASPECTS (focusing on the ischemia extent) ( 5 ). The second part was items yielded from the novel Rotterdam CT Score (focusing on the occupying effect) ( 9 ). The status of basal cisterns, midline shift, sulcal effacement, and types of mass lesions or intracranial hemorrhage were preceding reported items in the novel Rotterdam CT Score.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has demonstrated that sulcal effacement at the vertex is a reliable predictor of elevated ICP following TBI. 11 One of the purposes of this study was to ascertain the incidence of ABS associated with ASDH, encompassing hemispheric and whole-brain swelling. Therefore, we proposed novel CT-based criteria to clearly define this easily overlooked subtype of TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of post-traumatic ABS was made on the basis of CT findings. In addition to examining the basal cisterns, an additional evaluation of sulcal effacement at the vertex 11 was also conducted using axial sequences of CT with a thickness of 5 mm. If necessary, both axial and coronal sequences of thinner CT were utilized to determine the status of the sulci and cisterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation